Real Time Home-security Monitoring Using Smartphone Based IoT - Siregar, M. Taufiq Wahyudi; Sunardi, Sunardi (Signal and Image Processing Letters, 2022)
One of the most widely used security systems is the CCTV. The use of CCTV is not only as a security system on multistory buildings or offices, but also has already graduated homes are mainly in big cities where sometimes living functions aren't can be felt as comfortably as possible. This is happening because it is concerns the living owners who haven't been able to monitor in person thorough. Therefore, CCTV cameras are required for viewing it used to monitor home security conditions. The study uses IoT-based automation method, among others  hardware design of CCTV boxes, 3d CCTV camera design, system wiring, and layout boards. Software design includes block diagram and flowchart the system. The testing of the tool work is deploy on ESP32-cam, ultrasonic sensor, PIR sensor, and buzzer. The research was able to build a home security monitoring system from a long distance based on a IoT in real time. Remote test results obtained average HC-SR04 ultrasonic sensor error with a standard roll gauge 1.18%.